Sosialisasi Pemilihan Jenis Tanaman Pada Tanah Ber-pH Asam Dalam Upaya Peningkatan Produktivitas Lahan Pertanian Di Dusun Karanjang Ambon - Sahupala, Andjela; Irwanto, Irwanto (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
Acidic soil with pH < 6 is one of the main constraints in agricultural development in tropical areas, including in Karanjang Hamlet, Wayame Village. This condition causes low nutrient availability and metal toxicity that inhibits plant growth. This community service aims to increase farmers' knowledge about selecting plant species that are tolerant to acidic soil and land management techniques. The method used is a participatory approach through extension, demonstration, and hands-on practice involving 30 farmers in Karanjang Hamlet. Extension activities were conducted on May 23, 2025, with materials covering characteristics of acidic soil, pH effects on plants, tolerant plant species, and soil amelioration techniques. The results showed a 75% increase in farmers' knowledge about acid-tolerant plants such as cassava, corn, peanuts, and coffee. Practice evaluation showed that 80% of participants were able to identify symptoms of soil acidity and apply liming techniques and organic matter application. This program successfully increased farmers' awareness about the importance of acidic soil management for sustainable agricultural productivity.